2021
DOI: 10.1155/2021/6639763
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pathologic Complete Response following Neoadjuvant Chemotherapy ± Trastuzumab in Locally Advanced Breast Cancer

Abstract: Purpose. This study was designed to examine the relationship between breast cancer molecular subtypes and pathological response to neoadjuvant chemotherapy (NAC) ± trastuzumab, in locally advanced breast cancer (LABC). Methods. Female patients with LABC (T2–T4, N0–N2, and M0) who received neoadjuvant chemotherapy + trastuzumab if HER2+ subtype, followed by surgery and radiotherapy ± hormonal therapy, were identified. The primary endpoint was pathologic complete response (pCR) in the breast and axilla (ypT0/ypN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The prognostic value of pCR after NACT depends on the molecular subtype of breast cancer 49 ; TNBC and HER2-enriched patients have higher pCR rates than luminal breast cancer. 50 Thirty-three (29.2%) patients achieved pCR, 9 (7.9%) had luminal breast cancer, 21 (18.6%) had HER2 overexpression tumors, and 3 (2.7%) had TNBC. 51 , 52 …”
Section: Discussionmentioning
confidence: 96%
“…The prognostic value of pCR after NACT depends on the molecular subtype of breast cancer 49 ; TNBC and HER2-enriched patients have higher pCR rates than luminal breast cancer. 50 Thirty-three (29.2%) patients achieved pCR, 9 (7.9%) had luminal breast cancer, 21 (18.6%) had HER2 overexpression tumors, and 3 (2.7%) had TNBC. 51 , 52 …”
Section: Discussionmentioning
confidence: 96%
“…pCR is directly related to subtypes of HBC, and research is ongoing into the use of molecular subtypes in HBC to predict the clinical efficacy of NAC 33 . pCR rate was found to be very low in ER‐positive and HER2‐negative patients in HBC, and it was observed that the best responses to NAC were obtained in HER2‐positive patients, followed by triple‐negative breast cancer (TNBC) patients 34 . The pCR rates in Luminal A and B subtypes are expressed as 0.3%–6% and 8.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…33 pCR rate was found to be very low in ER-positive and HER2-negative patients in HBC, and it was observed that the best responses to NAC were obtained in HER2-positive patients, followed by triple-negative breast cancer (TNBC) patients. 34 The pCR rates in Luminal A and B subtypes are expressed as 0.3%-6% and 8.3%, respectively. The CR rate is 7.1% in the Luminal A subtype.…”
Section: Adverse Effects Ac Paclitaxelmentioning
confidence: 99%
“…Similar to the response of the primary cancer in the breasts, the biopsy-proven positive axillary lymph nodes may achieve a pCR to neoadjuvant systemic therapy. Rates of 47-79% axillary nodal pCR are commonly reported, especially in triple negative or HER2 overexpressed invasive breast cancer [30][31][32][33][34]. If axillary nodal pCR is suspected based on the clinical/radiological response, the options for axillary staging include ALND, SLNB, excision of marked axillary nodes and targeted ALND.…”
Section: Discussionmentioning
confidence: 99%